2020
DOI: 10.1016/j.artd.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated With Higher Risk of Wound Complications After Total Hip Arthroplasty

Abstract: Background: Obesity is prevalent among patients undergoing total hip arthroplasty and has been associated with the risk of wound complications, particularly when an anterior approach is used. However, most studies have focused on obesity defined by the body mass index (BMI), without considering the metabolic effects of adiposity. Thus, in this study, we investigated the independent effects of the BMI and metabolic syndrome on wound complications after total hip arthroplasty. Methods: Among 804 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The Xie et al study, which analyzed the impact of MetS on post-operative outcomes after ankle fracture, observed differences that approached statistical significance (p = .054), but ultimately fell short [8]. Conversely, Cheng et al found no significant differences (p = 0.70) in operative time for MetS and non-MetS patients undergoing total hip arthroplasty [7]. This finding is subject to scrutiny, given that fracture classification is not an available variable in the ACS-NSQIP study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Xie et al study, which analyzed the impact of MetS on post-operative outcomes after ankle fracture, observed differences that approached statistical significance (p = .054), but ultimately fell short [8]. Conversely, Cheng et al found no significant differences (p = 0.70) in operative time for MetS and non-MetS patients undergoing total hip arthroplasty [7]. This finding is subject to scrutiny, given that fracture classification is not an available variable in the ACS-NSQIP study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Cheng et al. found no significant differences (p = 0.70) in operative time for MetS and non-MetS patients undergoing total hip arthroplasty [ 7 ]. This finding is subject to scrutiny, given that fracture classification is not an available variable in the ACS-NSQIP study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that wound complications remain elevated in gout patients after controlling for numerous gout-associated comorbidities, such as obesity and peripheral arterial disease, which are associated with interrupted tissue healing. 2 24) Additionally, in an animal study, rats with an artificially induced gouty ulcer, when compared with the control group, demonstrated delayed wound healing with associated signs of chronic MSU crystal deposition, tophi ulceration, and chronic inflammatory responses. 25) …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated the association between metabolic syndrome and postoperative complications following orthopedic surgeries. Cheng et al found a four-fold increased risk of postoperative wound infection following total hip arthroplasty in patients with metabolic syndrome [ 5 ]. A systematic review and meta-analysis by Guofeng et al found that metabolic syndrome was associated with a higher risk of cardiovascular complications, surgical site infections, urinary tract infections, and 30-day readmission following total hip and total knee arthroplasty [ 6 ].…”
Section: Introductionmentioning
confidence: 99%